Urban microclimate in temperate climates: a summary for practitioners - Rohinton Emmanuel (Buildings & Cities, 2021)
A summary is presented of current knowledge and key considerations in urban climate mitigation that have a bearing on planning practice in temperate climates. Urban climate is the intended or unintended local climate consequence of planning decisions at the street, neighbourhood and even city scales. Such local climate change adds to the changing global climate, where it both interacts with as well as exacerbates the human, energy, built environment and urban consequences of climate change. Although a relatively new field of study, knowledge about urban climate has sufficiently grown in recent decades to be of practical value to decision-making in the design and planning arenas. The climatic, wellbeing and carbon impacts of urban climate change are summarised along with best practices in mitigation and their relative merits. Key action points involve mapping heat vulnerability as well as enhancing heat resilience. It is hoped this briefing note will raise awareness of the wide range of issues involved in responding to the urban climate anomaly, whether in planning new districts or infilling existing ones.